2008
DOI: 10.1007/s10038-008-0323-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in the EDA gene associated with X-linked recessive isolated hypodontia

Abstract: Isolated hypodontia, or congenital absence of one to six permanent teeth (OMIM 300606), is a common condition that affects about 20% of individuals worldwide. We identified two extended Pakistani pedigrees segregating X-linked hypodontia with variable expressivity. Affected males show no other associated anomalies, and obligate carrier females have normal dentition. We analyzed the families with polymorphic markers in the ectodysplasin A (EDA) gene region and obtained significant linkage to the phenotype in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Similar phenotypes are also described in patients with mutations in the EDA receptor (EDAR) gene or, in rare cases, the downstream signaling mediator EDAR-associated death domain (EDARADD) gene [Headon et al, 2001;Chassaing et al, 2006Chassaing et al, , 2010Bailleul-Forestier et al, 2008b;Mikkola 2009]. Mutations in the EDA and EDAR genes have also been shown to cause isolated hypodontia [Tao et al, 2006;Fan et al, 2008;Han et al, 2008;Rasool et al, 2008;Azeem et al, 2009;Mues et al, 2009a;Nieminen, 2009;Song et al, 2009].The aim of the present study was to investigate a cohort of young, unrelated individuals with isolated oligodontia for the prevalence of mutations in the AXIN2, MSX1, PAX9, EDA, and EDAR genes as well as in the novel candidate gene EDARADD. We also searched for genotype-phenotype correlations in carriers of mutations.…”
mentioning
confidence: 79%
“…Similar phenotypes are also described in patients with mutations in the EDA receptor (EDAR) gene or, in rare cases, the downstream signaling mediator EDAR-associated death domain (EDARADD) gene [Headon et al, 2001;Chassaing et al, 2006Chassaing et al, , 2010Bailleul-Forestier et al, 2008b;Mikkola 2009]. Mutations in the EDA and EDAR genes have also been shown to cause isolated hypodontia [Tao et al, 2006;Fan et al, 2008;Han et al, 2008;Rasool et al, 2008;Azeem et al, 2009;Mues et al, 2009a;Nieminen, 2009;Song et al, 2009].The aim of the present study was to investigate a cohort of young, unrelated individuals with isolated oligodontia for the prevalence of mutations in the AXIN2, MSX1, PAX9, EDA, and EDAR genes as well as in the novel candidate gene EDARADD. We also searched for genotype-phenotype correlations in carriers of mutations.…”
mentioning
confidence: 79%
“…Recently, there have been several reports of mutations in the EDA-A1 gene leading to an isolated form of X-linked recessive hypodontia (XLRH) [7,10,11,12]. This observation was somewhat surprising, since perturbation of the EDA-A1 pathway is also implicated in the development of hair and sweat glands.…”
Section: Introductionmentioning
confidence: 92%
“…The mutations in EDA-A1 causing isolated X-linked hypodontia are V365A, Q358E, D316G, T338M, M364T, G255C, G291R, A259E, R289C, Arg334His and S374R [7,10,11,12,16,17]. It is noteworthy that most mutations causing isolated XLRH are missense mutations that lie within the TNF homology domain.…”
Section: Discussionmentioning
confidence: 99%
“…Very rarely mutations in the same gene underlie an isolated hypodontia. To date, seven families with X‐linked hypodontia have been reported with causative mutations in the EDA gene 5,7–10 . The missense mutation, p.Q331H, identified in the present family is the seventh mutation in the EDA gene, which resulted in isolated hypodontia.…”
Section: Discussionmentioning
confidence: 54%
“…2007) 6 . Few recent reports indicated that certain mutations in the EDA gene result in X‐linked recessive isolated hypodontia as well 5,7–9 . The hypodontia affects mainly incisors and to some extent canines and premolars with a variable expression.…”
Section: Introductionmentioning
confidence: 99%